(Un-)konventionelle Methoden zur Finanzierung der Ampelpläne; (Un)conventional methods for financing the coalition plans - Jens Südekum (Wirtschaftsdienst, 2022)
– The new German government plans to increase investment spending considerably, yet without increasing taxes or reforming the debt brake enshrined in the constitution. This article explores the government's (un)conventional approaches to squaring this circle.
Keywords: H60; H30; 330; Finanzpolitik; Öffentliche Investition; Haushaltskonsolidierung; Deutschland